Rāja tejomayī Mahārāṇīśrī Vikṭoriyānuṃ jīvanacaritra - Desāī, Īcchārāma Sūryarāma, 1853-1912 (SAMP early 20th-century Indian books project ;, 1907)
Biography of Victoria, Queen of Great Britain, 1819-1901.